A case series of medically managed Candida parapsilosis complex prosthetic valve endocarditis - Penghao Guo; Yuting He; Rui Fan; Zhongwen Wu; Yili Chen; Yuli Huang; Kang Liao; Peisong Chen (BMC, 2021)
Abstract Background In recent years, Candida parapsilosis is recognized as a species complex and is composed of Candida parapsilosis sensu stricto, Candida orthopsilosis and Candida metapsilosis. Candida parapsilosis complex prosthetic valve endocarditis (PVE) is rare and the survival rate is still low despite of optimal therapeutic strategies. In our report, it is novel to report cases as Candida parapsilosis complex PVE at species and identify Candida parapsilosis using MALDI-TOF MS. Case presentation A series of 4 cases of Candida parapsilosis complex PVE from our institution was reported. Three were infected by Candida parapsilosis sensu stricto and one was infected by Candida metapsilosis. The condition of two cases got better and the other died. Conclusions More attention should be paid to Candida parapsilosis complex PVE and early diagnosis and prompt antibiotic therapy may play a role in the treatment for Candida parapsilosis complex PVE. It is recommended to identify Candida parapsilosis complex at species level and MALDI-TOF MS as an easy, fast and efficient identification method is worth promoting in clinical microbiology